Students’ Mathematical Representation Ability in Word Problems with Learning Cycle 7E Based on Cognitive Style - Rofiq, Eka Ahmad; Rochmad, Rochmad; Cahyono, Edy (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe students’ mathematical representation ability in word problems with learning cycle 7e based on cognitive style. The research method is a mixed method with a sequential explanatory model. The population of this study was students of class XII SMA Negeri 7 Semarang in the academic year 2020/2021 with class XII MIPA 3 as the experimental class, and class XII MIPA 2 as the control class. The data were collected using tests, documentation, questionnaires, observations, and interviews. The quantitative data were tested using the average test, the proportion test, the average difference test, the different proportions test, and the linear regression test, while the qualitative data were tested with data validity, data reduction, data representation, and draw a conclusion. Students with field-independent category were able to present ideas or information from a representation, create equations or mathematical models (mathematical ideas) from representation that had been made, complete tasks involving mathematical equations or models, write representations of solving mathematical problems in words. Students with field-dependent category were able to present ideas or information from a representation, create equations or mathematical models (mathematical ideas) from the representations that had been made.